(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Literature sources and earlier researches state that plants may be able to produce a variety of air ions, including negative light ions. In this article, the regularity of influence of plants on the number of ions in the room is being proved, basing on a series of experiments performed with the following plants: Spathiphyllum, Scindapsus, Strobilanthes, Chlorophytum and Pinus mugo. It was concluded that plants, in general, are able to stabilize the indoor ion concentration and reduce its fluctuations. The plants help to increase the concentrations of negative ions and decrease the concentration of positive ones, however the optimal and “healthy” ion concentration was not reached. Plants without artificial illumination work more as ion reducers, not producers.